Substratism: The Material Continuity of Being - Reavis, Marques A. (Journal of NeuroPhilosophy, 2026)
Substratism is a neurophilosophical framework in personal identity and consciousness studies. It addresses a category error common to discussions of consciousness and death: the conflation of the cessation of conscious organization with the termination of material existence. The framework maintains three strictly distinct categories. Being is the historically continuous material substrate that participated in the consciousness-enabling biological organization of the person. Entity is the autopoietic living organism. Identity is the arousal-enabled conscious organization instantiated upon that substrate during life. Death dissolves Identity and typically Entity, but does not annihilate Being. In this framework, the phrase scientific afterlife refers only to the lawful postmortem persistence, dispersal, and possible biological re-entry of the historical material substrate that constituted a person. It does not refer to memory survival, soul survival, personality continuation, resurrection, reincarnation, religious afterlife, near-death experience, paranormal survival, or any uninterrupted subjective continuation of experience. The phrase is a bounded technical term, not a metaphysical or religious claim. Brainstem-thalamic arousal systems are treated as necessary enabling conditions for wakeful conscious presence, not as sufficient generators of full human identity. The locus coeruleus is a candidate low-turnover marker within a distributed ascending arousal system, not the seat of selfhood or consciousness. If a different consciousness-enabling tissue better satisfies the retention and functional criteria, the candidate substrate must be relocated and the locus-coeruleus-specific version of the hypothesis is treated as falsified. The article proposes a staged research program of experimental protocols, to be preregistered before any future data collection, designed to test atom retention in candidate macromolecules, arousal-system dependence in disorders of consciousness, and ecological re-entry of historical material substrate. No new data are reported. The contribution is to make material-token continuity philosophically explicit, distinguish it from psychological, narrative, organismal, and pattern-copy accounts of personal identity, and specify the empirical conditions under which substrate continuity within consciousness-enabling biology can be tested or constrained.